Empirical Assessment of Economic Growth and Armed Conflict on Poverty in Yemen - Faisal Ali Mohammed Ali; Mansour A. Abdulwasaa (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2025)
This study examines the relationship between Economic growth, conflict and poverty using quantitative and regional data, including a comprehensive case study of Yemen. Poverty situation in Yemen is a special scenario that is beyond human reasoning because the nation is endowed with numerous material resources, but more than two-third of its population is living in abject poverty. This study examines the impact of economic growth on poverty in Yemen using secondary data spanning from (1994 to 2020). We also examine the impacts of conflict on Poverty. Poverty is an extremely pressing issue today, as it affects the vast majority of people during armed conflicts in Yemen have been ongoing since (2015). paper relies on a large and growing literature that provides evidence on the devastating impact that conflict has on poverty. The Ordinary Least Squares (OLS) approach was applied. The findings demonstrate that Yemen's poor and erratic GDP growth, along with prolonged political instability and civil wars, has resulted in a large increase in poverty rates. According to the statistical findings, economic growth has a significant negative impact on poverty, while years of conflict exacerbate poverty levels considerably. Comparative findings from Rwanda's post-conflict recovery highlight the importance of institutional and governance reforms, human capital investment, improved security, entrepreneurial activity, and solid economic policies for long-term poverty reduction. The study provides evidence-based recommendations for policymakers on how to promote inclusive economic growth, improve social protection, stabilize political conditions, and invest in infrastructure and human development, paving the way for Yemen to move away from conflict-induced poverty and towards sustainable development.